The 6-PACK programme to decrease fall-related injuries in acute hospitals: Protocol for a cluster randomised controlled trial - Barker, A.; Brand, C.; Haines, T.; Hill, Keith; Brauer, S.; Jolley, D.; Botti, M.; Cumming, R.; Livingston, P.; Sherrington, C.; Zavarsek, S.; Morello, R.; et al. (2011)
Background and aims: In-hospital fall-related injuries are a source of personal harm, preventable hospitalisation costs, and access block through increased length of stay. Despite increased fall prevention awareness and activity over the last decade, rates of reported fall-related fractures in hospitals appear not to have decreased. This cluster randomised controlled trial (RCT) aims to determine the efficacy of the 6-PACK programme for preventing fall-related injuries, and its generalisability to other acute hospitals. Methods: 24 acute medical and surgical wards from six to eight hospitals throughout Australia will be recruited for the study. Wards will be matched by type and fall-related injury rates, then randomly allocated to the 6-PACK intervention (12 wards) or usual care control group (12 wards). The 6-PACK programme includes a nine-item fall risk assessment and six nursing interventions: ‘falls alert’ sign; supervision of patients in the bathroom; ensuring patient's walking aids are within reach; establishment of a toileting regime; use of a low-low bed; and use of bed/chair alarm. Intervention wards will be supported by a structured implementation strategy. The primary outcomes are fall and fall-related injury rates 12 months following 6-PACK implementation. Discussion: This study will involve approximately 16 000 patients, and as such is planned to be the largest hospital fall prevention RCT to be undertaken and the first to be powered for the important outcome of fall-related injuries. If effective, there is potential to implement the programme widely as part of daily patient care in acute hospital wards where fall-related injuries are a problem.